Hubungan Efikasi Diri dengan Tingkat Kecemasan Perawat pada Masa Pandemi Covid-19 di Provinsi Nusa Tenggara Barat: Relationship between Self Effication and Nurse Anxiety During The Covid-19 Pandemic in West Nusa Tenggara Province - Suhamdani, Haris; Wiguna, Reza Indra; Hardiansah, Yayan; Husen, Lalu Muhammad Sadam; Apriani, Lia Arian (Bali Medika Jurnal, 2020)
Introduction: Nurses as the frontliners in handling Covid-19 could have a high risk of transmission. This could cause psychological problems in the form of anxiety. The existence of self-efficacy can help nurses carry out nursing care at times like this. This study aims to determine the relationship between self-efficacy and anxiety levels in nurses in West Nusa Tenggara Province. Methods: This study uses a quantitative correlation method with a cross-sectional approach. The study was conducted on April 13-25 2020, with 53 nurses as respondents. The instruments used were the General Self-Efficacy Scale (GSES) to measure self-efficacy and the General Anxiety Dissorder-7 (GAD-7) to measure the level of anxiety. Results: Based on the statistical test, it was obtained p = 0.006 (<0.05), meaning that there was a significant relationship between self-efficacy and anxiety levels of nurses during the COVID-19 pandemic in NTB Province. Conclusion: High self-efficacy can significantly relieve psychological symptoms such as anxiety levels in nurses during the COVID-19 pandemic.